Organic phosphorus in the environment - Turner, Benjamin L.; Frossard, Emmanuel; Baldwin, Darren S. (CAB books., 2005)
Organic phosphorus is involved in almost every biological process and is essential for life. However, the role of organic phosphorus and mechanisms for its dynamics has been poorly understood.